KEMAMPUAN KONEKSI MATEMATIS SISWA DENGAN PENDEKATAN LOOKING BACK DALAM MATERI ARITMATIKA SOSIAL - Yunika, Veny; Yani T, Ahmad; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract The problem in this thesis was How is the ability of mathematical connections of students with a looking back approach in solving social arithmetic material problems in class VII SMP N 2 Sungai Raya in 2018/2019 ?. The research method used was exploratory method. Subjects in this study were 6 out of 28 students selected based on the results of tests of student?s mathematical connection abilities with a looking back approach. The data collection techniques were using test and non-test (interview). Data collection tools in the form of tests of students? mathematical connection abilities with a looking back approach and interviews to dig deeper about students' mathematical connection abilities with a looking back approach. The results are : some indicators of connection capability of the looking back approach which was described using the first answer type. The process of re-checking the solution was shown by testing the percentage of profit, the percentage of loss, or the selling price that has been obtained so as to produce a known purchase or selling price in the problem, find another way, fabricate another problem with a different number with the right workmanship procedure and can find new, more efficient way. Keywords: Looking Back Approach, Mathematical Connection, Social Arithmetic